2014
DOI: 10.5897/ajmr2014.6755
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antioxidant activities of red onion, garlic and leek in sausage

Abstract: This study was designed to evaluate antimicrobial and antioxidant effect of ethanolic and aqueous extracts and essential oils of red onion, garlic and leek against Escherichia coli O 157 :H 7 ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
(32 reference statements)
2
10
1
1
Order By: Relevance
“…The highest level of phenolics were found in both A. sativum and A. cepa EOs (463.38 ± 1.24 and 429.33 ± 1.31 μg AAE/mg), while the lowest contents were recorded in the EOs of D. gossweileri stem barks and P. brazzeana roots (365.38 ± 0.66 μg AAE/mg and 342.20 ± 0.99 μg AAE/mg). These results do not match with those of Abdel-Salam et al [ 60 ] who showed that TPC of red A. sativum are lower than those of red A. cepa .…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…The highest level of phenolics were found in both A. sativum and A. cepa EOs (463.38 ± 1.24 and 429.33 ± 1.31 μg AAE/mg), while the lowest contents were recorded in the EOs of D. gossweileri stem barks and P. brazzeana roots (365.38 ± 0.66 μg AAE/mg and 342.20 ± 0.99 μg AAE/mg). These results do not match with those of Abdel-Salam et al [ 60 ] who showed that TPC of red A. sativum are lower than those of red A. cepa .…”
Section: Resultscontrasting
confidence: 94%
“…Thus, the EOs were found to be better antioxidants. These results are in agreement with the findings of Agnaniet et al [ 56 ], Ngono [ 32 ] and Mnayer et al [ 52 ], but in disaccordance with those found by Ndoye [ 40 ], Nyegue et al [ 42 ], Lee et al [ 24 ] and Abdel-Salam et al [ 60 ]. Mnayer et al [ 52 ] showed that Allium sativum EO was a more effective DPPH radical scavenger (SC 50 = 7.67 mg/mL) than Allium cepa EO (SC 50 = 20.19 mg/mL).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…al. [31] who stated that Salmonella typhimurium was more susceptible to aqueous extracts of red onion than E.coliO157:H7 at concentrations of 40 and 60 mg/ml, but both organisms showed similar sensitivity to garlic extracts. Iwalokun et.…”
Section: Figure7 Tem Image Of Prepared Cao Nps (Cao Nps In the Rangementioning
confidence: 99%
“…Increasing consumer awareness and health consciousness, however, has resulted in pressure to avoid utilising synthetic additives, which necessitates the use of natural additives to extend shelf-life and improve product safety (Descalzo and Sancho, 2008;Wojciak et al, 2011;Velasco and Williams, 2011;Savanovic et al, 2014a). The exploration and application of natural products that have antioxidant and antibacterial activities in meat products could be desirable and very useful to extend their storage shelf-life and perhaps aid in prevention of foodborne diseases (Hromis et al, 2014;Kumar and Tanwar, 2011;Abdel-Salam et al, 2014). Sources of natural antioxidants usually are spices, herbs, teas, oils, seeds, cereals, cocoa shell, grains, fruits and vegetables (Mata et al, 2007;Karabacak and Bozkurt, 2008;Opara and Al-Ani, 2010;Maciel et al, 2011;Ozvural et al, 2016).…”
Section: Introductionmentioning
confidence: 99%